Dramatic Efficacy of Interferon and Vemurafenib on Psychiatric Symptoms Revealing BRAFV600E-Mutated Erdheim–Chester Disease: A Case Report - Razanamahery, Jérôme; Abdallahoui, Maroua; Chabridon, Guillaume; Fromont, Agnès; Tarris, Georges; Idbaih, Ahmed; Comby, Pierre Olivier; Godard, Francois; Haroche, Julien; Audia, Sylvain; Bonnotte, Bernard (Frontiers in Immunology, 2022)
Erdheim-Chester disease (ECD) is a rare condition with underestimated neurological involvement. Psychiatric symptoms have not been described to date in the clinical spectrum of neuro-ECD. We here describe the first patient with psychiatric manifestations of delirium that revealed ECD with neurological involvement with favorable evolution under interferon and BRAF inhibitor. An 81-year-old woman was referred to the hospital because of severe cognitive impairment and cerebellar syndrome. Brain magnetic resonance imaging showed FLAIR hyperintensity lesions in the pons and upper cerebellum peduncles. Blood and cerebrospinal fluid (CSF) analysis were normal except for an elevated neopterin level in the CSF. Whole-body CT scan (18FDG-PET) showed peri-nephric fat infiltration and aorta adventitia sheathing with radiotracer uptake in the pons, vessels, peri-nephric fat, and bone lesions, which was characteristic of ECD. The diagnosis was confirmed on perirenal tissue biopsy, which also showed a BRAFV600E mutation. Treatment with interferon resulted in resolution of delirium, and BRAF inhibitor subsequently resulted in partial remission of all active sites. This case highlights that delirium can be the first manifestation of neurodegenerative ECD. Interferon and targeted therapy appear to be effective in this situation.